From Stage to Screen: Analysis of Women's Commodification in Dangdut Koplo via TikTok - Sekartaji, Pembayun Retno Ambarsari; Riyanto, Edi Dwi; Afdholy, Nadya (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2024)
Dangdut is a genre of music that has evolved into a cultural phenomenon within Indonesian society, particularly among the middle and lower socioeconomic classes. Dangdut music first featured lyrics with significant meaning and later evolved into dangdut koplo. Dangdut koplo is frequently linked to a rapid tempo and captivating vocalists. The objective of this study is to examine the commodification of female dangdut koplo singers within TikTok app. The research employed a visual ethnography approach to examine the commodification of female dangdut singers, focusing on their dress, cosmetics, and body motions that were captured in the video. The result of this study shows that there are elements or concepts of commodification of biduanita in dangdut koplo videos in TikTok. When performing on the stage, the singers generally utilized clothing, makeup, and body movements, to attract money or saweran from the crowds and increase popularity with their attractiveness. However, when the clip of the performance is used by unofficial accounts that do not belong to the artists or their production companies, it becomes a form of commodity for these accounts to acquire popularity on TikTok through likes and views. The bodies of these biduanitas then transform into commodity objects on social media platforms, promoting the sexualization and objetification of female dangdut singers.